DESIGN AND MANUFACTURE OF SEAT GRINDING BENCH - Irwansyah Hasibuan; Haris Budiman; Yudi Samantha (Universitas Majalengka, 2021)
The working principle of grinding is a grinding stone rotates in contact with the workpiece so that erosion, sharpening, grinding, or cutting. The shape and size of the base material will certainly not correspond to the shape and dimensions of a machine component. On the purchase of a grinding seat, is not included as a complementary tool holder or frame grinding sitting, therefore grinding sitting placed on the floor. It is very uncomfortable in the use of grinding to sit. Therefore, it is necessary to have a tool or a place to put the grinding seated. Tools or place holder for grinding is expected to create more comfortable when sitting grinding process use. Making bench grinder can be done with a series of processes, ie material cutting, making holes, grinding and welding. The strength of the bench grinder that has been made is 29821.26 N so that it can be said that has created a bench grinder is able to sustain grinding.